Effects of Dietary Glycerol Monolaurate on Growth, Antioxidant Capacity and Lipid Metabolism in Cage-Farmed Pompano (Trachinotus ovatus) Juveniles - Lin, Huaxing; Tan, Beiping; Yang, Qihui; Chi, Shuyan; Wei, Hongjie; Wu, Yuancai; Ray, Gyan Watson; Yohana, Mpwaga Alatwinusa (Frontiers in Marine Science, 2022)
Glycerol monolaurate (GML), a representative fatty acid glyceride, was used to improve promote growth. This study investigated the effect of glycerol monolaurate in diets on growth, serum biochemical parameters, antioxidant capacity, liver morphology and lipid metabolism for juvenile pompano Trachinotus ovatus. Six groups of T. ovatus (Initial mean weight = 14.00 ± 0.70 g) were respectively fed six diets, containing GML levels of 0.00% (G0), 0.05% (G5), 0.10% (G10), 0.15% (G15), 0.20% (G20) and 0.25% (G25), respectively, for 8 weeks in floating cages (length: 1 m; width: 1 m; height: 2 m). The highest weight gain rate (WGR), specific growth rate (SGR) and protein deposit rate (PDR) were observed in the G15 group (P < 0.05). Muscle polyunsaturated fatty acid content was significantly increased in the G10, G15 and G20 groups compared to the G0 group (P < 0.05). Hepatic glutathione peroxidase (GSH-Px), total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) activities were significantly increased in the G10 and G15 groups compared to the G0 group (P < 0.05), whereas hepatic malondialdehyde (MDA) was significantly reduced in the G10 and G15 groups (P < 0.05). The alkaline phosphatase (AKP) activity was significantly higher in the G5, G10, G15 and G20 groups than in the G0 group (P < 0.05), with the highest AKP activity in the G15 group. Alanine aminotransferase (ALT) activity was significantly lower in the G10, G15, G20 and G25 groups than in the G0 group (P < 0.05). In addition, GML promoted lipid metabolism in juvenile T. ovatus by regulating serum lipid metabolism-related enzyme activity, significantly reducing liver fat deposition and regulating liver lipid metabolism-related genes. Based on the broken-line model of WGR and PDR corresponding to GML levels, the optimum addition level of dietary GML was estimated to be 0.14%-0.16% for juvenile T. ovatus. In conclusion, 0.15% GML significantly improved the growth performance, hepatic antioxidant ability, lipid metabolism and protecting the liver condition for juvenile pompano T. ovatus.